Hypercalcemic type of small cell carcinoma of the ovary - Ilić, Milena B.; Jovanović, Dalibor V.; Milosavljević, Miloš Z.; Stanković, Vesna; Djordjević, Gordana; Protrka, Zoran; Nedović, Jasmina; Mitrović, Slobodanka Lj. (Vojnosanitetski pregled, 2015)
Introduction. Extrapulmonary small cell carcinoma is a rare, prognostically bad tumor category. Primary, it can be localized in every organ, even in the ovary, where, due to its clinical specificities, it represents a challenge in diagnosis, as well as in therapy. Small cell ovarian carcinoma (SCOC) is biologically very aggressive malignant tumor of unknown histogenesis. We presented a rare case of SCOC with hypercalcemia of aggressive course and fatal outcome in a postmenopausal woman at International Federation of Gynecology and Obstetrics (FIGO) Ia stage. Case report. A 60-year-old woman, Caucasian, came to the doctor because of discomfort in the lower abdomen and pain of greater intensity in last few days. Ultrasound examination and CT scan of the abdomen confirmed the presence of large adnexal masses of cystic-solid appearance with the largest diameter of 13 cm, regular structure of the other gynecological organs, without verifying the existence of metastatic deposits. All the results of laboratory analysis gave normal values, except for calcium, which was elevated. Explorative laparotomy with complete hysterectomy, bilateral salpingo-oophorectomy, dissection of lymph nodes and omentectomy were conducted. Based on pathohistological analysis of the operative material, SCOC at FIGO Ia stage was diagnosed. No complications were observed in a postsurgery period and after 10 days the patient was discharged in a good condition and with normal calcemia. The treatment was continued with concurrent radiotherapy and chemotherapy. However, in spite of overall treatment, the disease progressed, and the patient died of disseminated metastatic disease, 26 months after the diagnosis. Conclusion. Small cell carcinoma localized in the ovary is generally a tumor category with bad prognosis depending on the stage of the disease.